2016
DOI: 10.1016/j.ajog.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Web-based comparison of historical vs contemporary methods of fetal heart rate interpretation

Abstract: We examined the agreement of fetal heart rate interpretation with a defined set of rules among a number of different obstetrics practitioners using 3 different statistical methods and found moderate-to-substantial agreement among the clinicians for matching the interpretation of the expert. This implies that the simpler Caldeyro-Barcia method may perform as well as the newer classification system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…Five articles assessed reliability in relation to rater experience 30,36,[41][42][43] and six in relation to rater profession (Tables S5-S10). 41,42,[44][45][46][47] In general, across the articles we did not find any clear association between rater experience or profession and reliability.…”
Section: Reliability and Agreement In Intrapartum Fetal Monitoringcontrasting
confidence: 54%
See 1 more Smart Citation
“…Five articles assessed reliability in relation to rater experience 30,36,[41][42][43] and six in relation to rater profession (Tables S5-S10). 41,42,[44][45][46][47] In general, across the articles we did not find any clear association between rater experience or profession and reliability.…”
Section: Reliability and Agreement In Intrapartum Fetal Monitoringcontrasting
confidence: 54%
“…Five articles assessed reliability in relation to rater experience 30,36,41–43 and six in relation to rater profession (Tables S5–S10). 41,42,44–47 In general, across the articles we did not find any clear association between rater experience or profession and reliability. In turn, we found three articles assessing reliability of FHR baseline, variability, and accelerations in relation to pre‐ and post‐training sessions, 44,48,49 where reliability and agreement were generally higher after training sessions.…”
Section: Resultsmentioning
confidence: 70%
“…[17] Concerning the variability in the interpretation of the FHR parameters, a study by Schiermeier et al demonstrated that only the baseline FHR showed a fair agreement (pa, 0.49-1.01) among 43 different obstetricians [18] and this has been corroborated by similar studies involving experts. [19] The main limitation of our study was certainly represented by the size of the sample, 40 healthcare professionals (11 gynecologists and 29 obstetricians).…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 95%
“…[5][6][7] Even when experienced clinicians use accepted guidelines, FHR interpretation has a low specificity and a low positive predictive value in detecting metabolic acidemia. [8][9][10][11][12][13] To prevent neonatal hypoxia and avoid unnecessary operative deliveries, adjunctive technologies have been developed to further assess fetal oxygenation.…”
Section: Introductionmentioning
confidence: 99%